Public Expenditure and Financial Accountability Assessment of Nakuru County, Kenya - World Bank (World Bank, Washington, DC, 2020)
The subnational Public Expenditure and Financial Accountability (PEFA) assessment seeks to ascertain the performance of the public financial management (PFM) system of county governments using the PEFA methodology. So far, the Government of Kenya has gained experience in the application of the PEFA methodology by undertaking four national PEFA assessments over the years, the latest carried out in 2017 and the report due for completion in 2018. However, this is the first subnational assessment to be carried out in Kenya following the adoption of a devolved system of government. It is notable that the national and subnational PEFA assessments are almost being done concurrently and this is important because both levels of government share the same PFM system implying that an evidence-based reform agenda can be implemented simultaneously after areas that require improvements are identified. The subnational assessments, which covered 6 out of 47 counties, have been jointly financed by the World Bank and International Development Research Centre (IDRC) through the Kenya Institute for Public Policy Research and Analysis (KIPPRA).